Protection of Constitutional Rights for Female Coastal Workers in Pekalongan Against Loss of Land Rights: An Agrarian Law and Islamic Law Approach - Pratami, Bunga Desyana; Minarsih, Minarsih; Ratna Intan, Sri Ratu (Al-Mazaahib: Jurnal Perbandingan Hukum, 2024)
This article examines the protection of the constitutional rights of Pekalongan's women coastal workers against the loss of land rights due to sea flooding. Based on data from the Pekalongan Regional Disaster Management Agency (BPBD), in the last five years, more than 40% of the land in this coastal area has been submerged, affecting women's livelihoods. The juridical problem is that the Basic Agrarian Law (UUPA) does not regulate state compensation for destroyed land. Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 3 of 2024 on Amendments to Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 17 of 2021 on Procedures for Determining Land Destruction states that land parcels affected by tidal floods in Pekalongan can be categorized as land destruction. Land rights holders are given priority for reconstruction or reclamation within one year and receive a kerohiman fund if the land is used or reconstructed by the government. This research uses agrarian law and Islamic law approaches to evaluate the existing legal protections. The results show that constitutional protection for coastal women workers in Pekalongan already exists, but there are still some weaknesses. In addition, the practice of such protection has not been maximized. Some of these things are the main causes of inadequate legal protection of the rights of women coastal workers. Islamic law provides a more inclusive perspective on property rights and social justice, but its implementation is limited. This research contributes to the understanding of agrarian regulations in providing protection and compensation for women coastal workers as well as the understanding of Islamic principles in maintaining justice and welfare for those affected by tidal floods.   Artikel ini mengkaji perlindungan hak konstitusional perempuan buruh pesisir pantai Pekalongan terhadap hilangnya hak atas tanah akibat rob. Berdasarkan data dari Badan Penanggulangan Bencana Daerah (BPBD) Pekalongan, dalam lima tahun terakhir, lebih dari 40% tanah di wilayah pesisir ini telah terendam, yang berimbas pada mata pencaharian perempuan. Masalah yuridis yang dihadapi adalah bahwa Undang-Undang Pokok Agraria (UUPA) tidak mengatur kompensasi negara bagi tanah yang musnah. Peraturan Menteri Agraria dan Tata Ruang/Kepala Badan Pertanahan Nasional Republik Indonesia Nomor 3 Tahun 2024 tentang Perubahan atas Peraturan Menteri Agraria dan Tata Ruang/Kepala Badan Pertanahan Nasional Nomor 17 Tahun 2021 tentang Tata Cara Penetapan Tanah Musnah menyatakan bahwa bidang tanah yang terdampak banjir rob di Pekalongan dapat dikategorikan sebagai tanah musnah. Pemegang hak atas tanah diberikan prioritas untuk rekonstruksi atau reklamasi dalam satu tahun dan mendapatkan dana kerohiman jika tanah digunakan atau direkonstruksi oleh pemerintah. Penelitian ini menggunakan pendekatan hukum agraria dan hukum Islam untuk mengevaluasi perlindungan hukum yang ada. Hasil penelitian menunjukkan bahwa perlindungan konstitusional bagi pekerja perempuan pesisir di Pekalongan sudah ada, tetapi masih terdapat beberapa kelemahan. Selain itu, praktik perlindungan tersebut belum maksimal. Beberapa hal inilah yang menjadi penyebab utama belum memadainya perlindungan hukum terhadap hak-hak perempuan buruh pesisir. Hukum Islam memberikan perspektif lebih inklusif tentang hak milik dan keadilan sosial, tetapi implementasinya terbatas. Penelitian ini berkontribusi pada pemahaman mengenai regulasi agraria dalam memberikan perlindungan dan kompensasi bagi perempuan buruh pesisir serta pemahaman prinsip-prinsip Islam dalam menjaga keadilan dan kesejahteraan bagi pihak yang terdampak banjir rob.